Homozygous missense mutation in the LMAN2L gene segregates with intellectual disability in a large consanguineous Pakistani family - Rafiullah, Rafiullah; Aslamkhan, Muhammad; Paramasivam, Nagarajan; Thiel, Christian; Mustafa, Ghulam; Wiemann, Stefan; Schlesner, Matthias; Wade, Rebecca C.; Rappold, Gudrun; Berkel, Simone (Journal of medical genetics, 2016)
Background Intellectual disability (ID) is a neurodevelopmental disorder affecting 1%-3% of the population worldwide. It is characterised by high phenotypic and genetic heterogeneity and in most cases the underlying cause of the disorder is unknown. In our study we investigated a large consanguineous family from Baluchistan, Pakistan, comprising seven affected individuals with a severe form of autosomal recessive ID (ARID) and epilepsy, to elucidate a putative genetic cause. - Methods and results Whole exome sequencing (WES) of a trio, including a child with ID and epilepsy and its healthy parents that were part of this large family, revealed a homozygous missense variant p.R53Q in the lectin mannose-binding 2-like (LMAN2L) gene. This homozygous variant was co-segregating in the family with the phenotype of severe ID and infantile epilepsy; unaffected family members were heterozygous variant carriers. The variant was predicted to be pathogenic by five different in silico programmes and further three-dimensional structure modelling of the protein suggests that variant p.R53Q may impair protein-protein interaction. LMAN2L (OMIM: 609552) encodes for the lectin, mannose-binding 2-like protein which is a cargo receptor in the endoplasmic reticulum important for glycoprotein transport. Genome-wide association studies have identified an association of LMAN2L to different neuropsychiatric disorders. - Conclusion This is the first report linking LMAN2L to a phenotype of severe ARID and seizures, indicating that the deleterious homozygous p.R53Q variant very likely causes the disorder.
Published Online First 13 November 2015
Gesehen am 17.07.2020